Evaluating the psychometric measurement properties of patient-reported outcome measures for uterine fibroids using the Consensus-based Standards for the selection of health Measurement Instruments (COSMIN) guidelines: a systematic review - Wei Yan; Fei Liu; Ya Li; Shixuan Wang; Minli Zhang; Wenwen Wang; Suzhen Yuan; Shuhao Yang; Qing Yan; Tao Xiang (BMJ Open)
Objectives To systematically evaluate the psychometric measurement properties of existing patient-reported outcome measures (PROMs) for uterine fibroids using the Consensus-based Standards for the selection of health Measurement Instruments (COSMIN) guidelines and to provide recommendations for the most appropriate tools in clinical and research settings.Design Systematic review using the COSMIN guidelines and the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach.Data sources The Medline, CINAHL, Embase and Web of Science databases were searched for relevant studies published up to 28 February 2025. Eligibility criteria were studies that targeted patients with uterine fibroids using a PROM instrument and were published as full-text, English-language articles in peer-reviewed journals. Studies that used only a portion or an unvalidated short form of the PROMs, non-English publication or non-peer-reviewed formats were excluded.Data extraction and synthesis Two independent reviewers extracted the data using EndNote V.X9 (Clarivate, London, UK). The PROM quality assessment adhered to the COSMIN guidelines. The level of evidence for the psychometric properties of each PROM was determined using a modified GRADE approach.Results Of 678 records retrieved in the literature search, 11 were included. Six uterine fibroid-specific PROMs were identified and evaluated according to the COSMIN guidelines. The Uterine Fibroid Symptom and Quality of Life (UFS-QoL) and the Bleeding and Pelvic Discomfort Scale (BPD) received class A recommendations (recommended) for sufficient content and structural and internal consistency. However, four other PROMs, namely the Perioperative Anxiety Scale for Uterine Fibroids, Fibroid Symptom Diary, Uterine Fibroid Daily Bleeding Diary and Menstrual Pictogram Superabsorbent Polymer-containing Version 3, received class B recommendations (further research required) due to poor measurement properties, including inadequate reliability and unquantified measurement error.Conclusion The results of the present study fill a knowledge gap in the systematic and comprehensive evaluation of uterine fibroid-related PROMs. These findings provide valuable insights and recommendations for clinicians and researchers seeking reliable PROMs for this patient population. The UFS-QoL and BPD were classified as ‘A’ and were recommended, demonstrating the potential to promote outcome measurements in future studies.PROSPERO registration number CRD42023474806.